Re-Connecting Voices. The (New) Strategic Role of Public Sector Communication After the Covid-19 Crisis - Lovari, Alessandro; D'Ambrosi, Lucia; Bowen, Shannon A. (PARTECIPAZIONE E CONFLITTO, 2020)
This article aims to investigate the evolution of public sector communication before and after the Covid-19 crisis that has strongly impacted governmental institutions, public policy, contemporary society, and media ecologies. After a review of the main characteristics of public sector communication, the article proposes an interpretative and dynamic model to better understand the new challenges for public institutions. The model introduces ethics as the new, primary driver for public sector communication to surround all decisions, pointing out the need for transparent, authentic participation and dialogue to build trust. Focusing on two dimensions (trust/distrust, openness/closedness), the authors investigate the main trajectories of change for public sector communication, conceiving the three pillars of open government (transparency, participation and collaboration) as strategic values for improving the quality and efficacy of communication. In this time of uncertainty, the new trajectories of communication should fully embrace an ethical approach in order to become resilient, able to respond to citizens' needs and expectations, and to maintain responsible relationships with media, varied strategic publics, and a rapidly changing global community.